Body mass index affects spirometry indices in patients with chronic obstructive pulmonary disease and asthma - Wang, Xiaohu; Gan, Hui; Wang, Yimin; Yu, Xinxin; An, Jiaying; Sun, Baoqing; Gao, Yi; Zhu, Zheng (Frontiers in Physiology, 2023)
Background Body mass index (BMI) is known to affect the outcomes of spirometry indices.However, its association with spirometry indices in COPD and asthma is less studied. We aimed to explore the impact of BMI on these patients.Patients with COPD or asthma who completed bronchodilator tests (BDTs) between 2017 and 2021 were reviewed. Spirometry indices were compared among patients with COPD or asthma that were subclassified as underweight (BMI< 18.5 kg/m2), normal weight (≥ 18.5 to < 25), overweight (≥ 25 to < 30), and obesity (≥ 30).Analysis was conducted on 3891 COPD patients (age:66.5±7.8 years) and 1208 asthma patients (age:59.7±7.5 years). COPD patients classified as underweight demonstrated significantly lower values of pre-and post FEV1 (L, %) ，pre-and post FVC (L, %)， and preand post-FEV1/FVC (all P < 0.05). In contrast, COPD patients who were overweight or obese exhibited higher values for pre-and post FEV1 (L, %), and pre and post FEV1/FVC (all P < 0.05). Within the cohort of asthma patients, those underweight had lower pre-and post FEV1 (L, %), pre and post FVC (L, %), pre and post FEV1/FVC %. Obese asthma patients displayed higher pre and post FEV1/FVC (all P < 0.05).Significant BMI category differences in spirometry indices can be seen in patients with COPD or asthma. Both underweight and obesity could affect the diagnosis and severity of these diseases. Recognizing these effects is essential to better management and diagnosis of these patients.